2016
DOI: 10.5489/cuaj.3225
|View full text |Cite
|
Sign up to set email alerts
|

Xanthogranulomatous pyelonephritis presenting as a pseudotumour

Abstract: Original research E36case series AbstractIntroduction: Xanthogranulomatous pyelonephritis (XGPN) is an atypical form of chronic pyelonephritis referred to as the ''great imitator'' because the clinical and radiological findings closely resemble other pathological entities, especially for the focal forms. Distinguishing focal XGPN from renal cancer is preoperatively difficult. Methods:We report a total number of 12 pseudotumoural XGPN cases diagnosed and treated in our department. The aim of this study is to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…Two forms of morphological involvement are reported; more common diffuse form which spread with pelvic communication and relatively rarer focal form within the renal cortex [5]. Since, focal form strictly mimics renal carcinoma; distinguishing focal XGP from renal cancer is preoperatively difficult [6].…”
Section: Discussionmentioning
confidence: 99%
“…Two forms of morphological involvement are reported; more common diffuse form which spread with pelvic communication and relatively rarer focal form within the renal cortex [5]. Since, focal form strictly mimics renal carcinoma; distinguishing focal XGP from renal cancer is preoperatively difficult [6].…”
Section: Discussionmentioning
confidence: 99%
“…A recently published case series of 12 XGPN [1] cases showed that only one patient presented with fever. Common presentations include a flank mass or flank pain.…”
Section: Discussionmentioning
confidence: 99%
“…The organism isolated was Escherichia coli, a gram negative organism, from the urine and blood, though in one-fourth of cases urine culture may be sterile [6]. The initial findings of left ureterohydronephrosis on a renal ultrasound and the totally distorted architecture with multiple non-enhancing sectors on computed tomography raised the possibilities of isolated xanthogranulomatous pyelonephritis, renal cell carcinoma or their coexistence [7] [8] [9] [10]. The treatment plan was to cover the patient with a course of antibiotics and to manage conservatively the renal failure, including a preoperative sessions of hemodialysis.…”
Section: Discussionmentioning
confidence: 99%